Development of a self-stressing NiTiNb shape memory alloy (SMA)/fiber reinforced polymer (FRP) patch. (18th May 2015) - El-Tahan, M; Dawood, M; Song, G
Abstract: The objective of this research is to develop a self-stressing patch using a combination of shape memory alloys (SMAs) and fiber reinforced polymer (FRP) composites. Prestressed carbon FRP patches are emerging as a promising alternative to traditional methods to repair cracked steel structures and civil infrastructure. However, prestressing these patches typically requires heavy and complex fixtures, which is impractical in many applications. This paper presents a new approach in which the prestressing force is applied by restraining the shape memory effect of NiTiNb SMA wires. The wires are subsequently embedded in an FRP overlay patch. This method overcomes the practical challenges associated with conventional prestressing. This paper presents the conceptual development of the self-stressing patch with the support of experimental observations. The bond between the SMA wires and the FRP is evaluated using pull-out tests. The paper concludes with an experimental study that evaluates the patch response during activation subsequent monotonic tensile loading. The results demonstrate that the self-stressing patch with NiTiNb SMA is capable of generating a significant prestressing force with minimal tool and labor requirements.